Problematika Pendidikan Islam Melayu Patani Thailand - Hifza Hifza; Aslan Aslan (Al-Ulum, 2019)
The problems of Islamic education in Patani Malay which began in the golden period, gradually decreased, when the Malay kingdom of Patani was taken over by the Thai kingdom. The research results of the study show that: First, Patani Malays who lived in parts of Southern Thailand had experienced a period of triumph so that many gave birth to clerical figures. Second, when Patani was taken over by the Siamese kingdom, the Islamic educational institutions had undergone changes consisting of three types, namely Islamic schools, madrassas, and Islamic boarding schools. Third, changes in Islamic educational institutions increasingly experienced changes when the change of Thai leaders, namely the assimilation of educational culture. Fourth, the government policy towards Patani Malay, which continues to trigger conflict, makes them set policies according to the wishes of the Patani people but the policy is experiencing a dilemma for Patani Malay.